Upaya Meningkatkan Kemampuan Kerjasama MelaluiKegiatan Memindahkan Bolasuara Secara EstafetPada Anak Didik Kelompok B Tk Pertiwi ITamanrejo Kecamatan Tunjungan Kabupaten Blora Tahun 2015 - SUSTINI, SRI; , Drs. M. Yahya, M.Si (2015)
This study aimed to describe the increase in the ability to cooperate through the method of play to move the ball on the child's voice in group B TK Pertiwi I Tamanrejo . This study was conducted in kindergarten Pertiwi I Tamanrejo District of Tunjungan. The subjects in this study is a learner group B TK Pertiwi I Tamanrejo Blora.Implementation of learning improvement is implemented through the use of voice activity move the ball given to all student learners group B TK Pertiwi I Tamanrejo through two cycles of learning . The method used is classroom action research ( PTK ), which consists of 2 cycles . Subjects were students learners TK Pertiwi I Tamanrejo as many as 25 of the Child. Data analysis using comparative descriptive analysis techniques by comparing the initial conditions with the results achieved in each cycle , and a qualitative descriptive analysis comparing the results of observas idengan observations and reflections on the pre-cycle , the first cycle , and second II. Based on the results of research supporting a research has been done and the results obtained data analysts in each cycle of learning , it was concluded that , through a credible form of moving the ball in the relay voice can improve children's ability to cooperate in group B TK Pertiwi I Tamanrejo. From the resulting increase in the ability to cooperate before the procedure showed an average yield of 52.67 % after the action on the first cycle increased by 23.28 % to 75.95 % . At the end of the second cycle increased by 14.22 % to 90.17 % . Such improvements have achieved an indicator of succes , get obtaining Developing criteria Very Good .